the PENGARUH PEMBERIAN SIMETIDIN TERHADAP PROFIL FARMAKOKINETIKA PARASETAMOL DENGAN METODE HIGH PERFORMANCE LIQUID CHROMATOGRAPHY (HPLC) TAHUN 2020 - Christica Ilsana Surbakti (Jurnal Penelitian Farmasi & Herbal, 2020)
Paracetamol is a safe analgesic and antipyretic drug with low side effects, effective and well tolerated. In some cases there is a drug interaction between paracetamol and other drugs. The purpose of this study is to determine the effect of cimetidine administration on paracetamol pharmacokinetic profiles. The method used in this study was an experimental method using 3 rabbits. Rabbits are divided into 3 groups. The first treatment group was given paracetamol suspension, the second treatment group was giving cimetidine 1 hour before paracetamol and the third group was giving cimetidine and paracetamol simultaneously. The dose of the drug has been adjusted to each rabbit. Measurement of plasma paracetamol drug levels was carried out using a High Performance Liquid Chromatography (HPLC) tool. The results of the study showed that the pharmacokinetic parameter values ​​did not show any significant effect on each group. Cimetidine administration simultaneously affects paracetamol pharmacokinetic parameters but not significantly. Likewise with the administration with a time span of 1 hour, did not show any significant changes in the pharmacokinetics of paracetamol.